Optimization of the size and launch conditions of a discus - Seo, K.; Shimoyama, K.; Ohta, K.; Ohgi, Y.; Kimura, Y. (Procedia Engineering, 2014)
This paper describes optimization of the size and launch conditions of a discus. The objective function for optimization is the flight distance. Longer flight distance is better. Fourteen design variables are considered. Eight of the fourteen are concerned with the skill of the thrower. They determine the launch conditions, which are controlled by the thrower when he or she throws. The other six variables are concerned with the design of the equipment. These are the dimensions of the discus (width, thickness, radius of the metal rim and diameter of the flat center area on each side), the moment of inertia on the axis of symmetry and finally the mass of the discus. The dependences of size and the angle of attack on the aerodynamic data are estimated by using CFD (computational fluid dynamics) technique. Typical CFD results, including the effect of stalling, were confirmed by comparing the results with experimental data. As a result, the longest flight distance that could be achieved was 79 meters. In order to do this, the initial yaw rate on the axis of symmetry should be maximized. The mass should be the smallest. The moment of inertia on the axis of symmetry, the diameter of the flat center area and the width should be designed to be large. The air inflow to the discus should arrive from the upper side at the very beginning of the flight.